Real exchange rate variability and the choice of exchange rate regime by developing countries - Savvides, Andreas (My University, 1990)
This paper draws together two distinct strands of the exchange rate literature. It proposes that real exchange rate variability and the choice of exchange rate regime are jointly determined. I test this claim by estimating a simultaneous limited-dependent variable model, with data from a cross section of developing countries during the recent floating period. Drawing on the relevant exchange rate literature, the paper examines a number of exogenous determinants of exchange rate variability and the choice of exchange rate regime.